2017
DOI: 10.1007/s13187-017-1302-8
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from the Young Breast Cancer Survivorship Network

Abstract: The Young Breast Cancer Survivors Network (Network) is an academic and community-based partnership dedicated to education, support, and networking. The Network used a multi-pronged approach via monthly support and networking, annual education seminars, website networking, and individual survivor consultation. Formative and summative evaluations were conducted using group survey and individual survivor interviews for monthly gatherings, annual education meetings, and individual consultation. Google Analytics wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…31 Previous studies have examined racial disparities in HPV knowledge. A recent study found that HPV knowledge and awareness was significantly lower among black women than white women 18 years and older, 32 and another study found that Hispanic and non-Hispanic black women were less aware of HPV infection and vaccination, and were also less likely to report having been vaccinated, than non-Hispanic white women. 33 In our study, 75% of the respondents reported to belong to a minority group and less than 10% reported to have a great deal of knowledge of HPV transmission (9%), HPV-related conditions (7%), HPV prevention (8%) and the HPV vaccine (6%).…”
Section: Discussionmentioning
confidence: 98%
“…31 Previous studies have examined racial disparities in HPV knowledge. A recent study found that HPV knowledge and awareness was significantly lower among black women than white women 18 years and older, 32 and another study found that Hispanic and non-Hispanic black women were less aware of HPV infection and vaccination, and were also less likely to report having been vaccinated, than non-Hispanic white women. 33 In our study, 75% of the respondents reported to belong to a minority group and less than 10% reported to have a great deal of knowledge of HPV transmission (9%), HPV-related conditions (7%), HPV prevention (8%) and the HPV vaccine (6%).…”
Section: Discussionmentioning
confidence: 98%
“…UAB boasted a thriving face-to-face evidence-based, education and support network for YBCS in Central Alabama (Gisiger-Camata, Nolan, Vo, Bail, Lewis, & Meneses, 2017). UAB’s network was locally funded and named the Young Breast Cancer Survivorship Network .…”
Section: Methodsmentioning
confidence: 99%